Uncontrolled hypertension due to volume overload contributes to higher left ventricular mass index in CAPD patients - KOÇ, MEHMET (OXFORD UNIV PRESS, 2002)
Background. Hypertension (HT) is common in patients on continuous ambulatory peritoneal dialysis (CAPD) and is responsible for increased cardiovascular morbidity and mortality. In this study, we aimed to determine the prevalence of 'uncontrolled HT' during background therapy in CAPD patients by using office measurements and ambulatory blood pressure monitoring (ABPM). We further determined whether intravascular volume status, assessed by inferior vena cava diameter (IVCD) index, contributes to higher blood pressure (BP) and increased left ventricular mass index (LVMI). Methods. Seventy-four CAPD patients were included in the final analysis. All patients underwent echo-cardiographic examination and received ABPM. Patients undergoing CAPD were categorized into two groups: 'uncontrolled HT' (Group A) and 'normotensive and controlled HT' (Group 13). Intravascular volume status was determined using the IVCD index and collapsibility index (CI) on the same day as ABPM. Results. The prevalence of HT was 84% when using office measurements and 82% when using daytime ABPM. Daytime BP was 147/92 mm Hg by office measurements and 145/91 mm Hg by ABPM (P>0.05). The prevalence of 'uncontrolled HT' measured by ABPM was 73% (n = 54). Patients with uncontrolled HT (Group A) were taking more antihypertensive medications than patients with 'normotension and controlled HT' (Group B, n = 20; 1.0+/-0.8 vs 0.5+/-0.7, P=0.008). The IVCD index was higher in Group A 2 than in Group B (9.2+/-2.1 vs 7.7+/-1.9 mm/m(2), P=0.007). There was no correlation between IVCD index and office BP, ABPM measurements or LVMI. The LVMI was also higher in Group A than in Group B (145+/-39 vs 118+/-34g/m(2), P<0.01). Stepwise multiple regression analysis revealed that 24 It diastolic BP and haemoglobin were independent determinants of LVMI. Conclusion. Uncontrolled HT on background therapy is highly prevalent among volume overloaded CAPD patients. Further long-term prospective studies examining effects of salt restriction and ultrafiltration on BP control and left ventricle wall thickness are warranted.
Keywords: CAPD; hypertension; inferior vena cava diameter (index); left ventricular hypertrophy; plasma volume overload; AMBULATORY BLOOD-PRESSURE; INFERIOR VENA-CAVA; STAGE RENAL-DISEASE; PERITONEAL-DIALYSIS; DRY-WEIGHT; SALT INTAKE; HEMODIALYSIS; HYPERTROPHY; CARDIOMYOPATHY; PREVALENCE